2017
DOI: 10.1002/cbic.201700240
|View full text |Cite
|
Sign up to set email alerts
|

Chemobacterial Synthesis of a Sialyl‐Tn Cyclopeptide Vaccine Candidate

Abstract: A conjugatable form of the tumour-associated carbohydrate antigen sialyl-Tn (Neu5Ac-α-2,6-GalNAc) was efficiently produced in Escherichia coli. Metabolically engineered E. coli strains overexpressing the 6-sialyltransferase gene of Photobacterium sp. and CMP-Neu5Ac synthetase genes of Neisseria meningitidis were cultivated at high density in the presence of GalNAc-α-propargyl as the exogenous acceptor. The target disaccharides, which were produced on the scale of several hundreds of milligrams, were then conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Binding to a Tn-specific antibody showed a distinct preference for specific arrangements on the MAP system. The same group has prepared similar systems bearing the sialyl-Tn TACA ( 208 ) as well as Tn conjugated in a natural linkage to serine and one replaced with an oxime unit, where they showed that the oxime-linked Tn had superior immunotherapeutic properties in vivo ( 209 ).…”
Section: Glyco-nanotechnology and Cancer Immunotherapymentioning
confidence: 99%
“…Binding to a Tn-specific antibody showed a distinct preference for specific arrangements on the MAP system. The same group has prepared similar systems bearing the sialyl-Tn TACA ( 208 ) as well as Tn conjugated in a natural linkage to serine and one replaced with an oxime unit, where they showed that the oxime-linked Tn had superior immunotherapeutic properties in vivo ( 209 ).…”
Section: Glyco-nanotechnology and Cancer Immunotherapymentioning
confidence: 99%
“…Glycolipids are found on the surface of all eukaryotic cells, where they extend from the phospholipid bilayer (lipid portion) into the extracellular environment (glycan portion) . Beyond their traditionally accepted roles as energy sources for living organisms, it is now well established that oligosaccharides play important roles in a variety of physiological and pathological processes; this includes but is not limited to cell growth and proliferation, immune responses, angiogenesis and tumor cell metastasis, toxin interaction, protein folding and degradation, cell–cell communications, and cell–pathogen interactions. Additionally, it has also been shown that aberrant glycosylations have a strong relationship with cancer and multiple other human diseases. For example, the truncated mucin-type O-glycans including Tn-antigen, sialyl-Tn antigen, T-antigen, and sialyl-T antigen have low or no expression on normal cells but are highly expressed in many human cancer cell lines. These tumor-associated carbohydrate antigens are targets for application in either clinical diagnosis or immunotherapy. …”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews describe very well the great advances in the field, particularly in the synthesis of N‐linked glycoproteins carrying complex antennary structures . Moreover, various efficient methodologies for the preparation of homogeneous O‐linked glycopeptides and glycoproteins have been recently developed, furnishing useful tools for biological studies and for potential therapeutic applications, such as cancer vaccines . Also, short, nonconventional N‐linked glycans that can be mainly found in bacteria and archaea have attracted attention for their possible interactions in binding events related to infections.…”
Section: Introductionmentioning
confidence: 99%